Antiseptics solutions for Prevention of surgical wound infection in appendectomized patients by complicated acute appendicitis: Soluciones antisépticas en la prevención de infección de herida quirúrgica en pacientes operados por apendicitis aguda complicada - García Galicia, Arturo (2023)
Surgical wound infection secondary to complicated acute appendicitis is frequent. The objective was to compare the Dakin and the Superoxidative solutions to prevent surgical wound infections in complicated acute appendicitis. It was a comparative, cross-sectional study, in 104 patients with complicated acute appendicitis (medium age 36.29 years, 69(66.43%) men). Group 1: 52 patients with surgical wound lavage with Dakin modified solution. Group 2: 52 patients with superoxidative solution (Microdacyn®). All patients received ceftriaxone 1 g before surgery; conventional appendectomy was performed and the wall closure with Vicryl 1 and Nylon 2/0. Surgical wound was evaluated 7 days after surgery, looking for pus, edema, erythema, local heat. X2 and Student's t were used. Surgical wound infection was present in 11 (10.6%) patients, 3(5.8%) patients from group 1 and 8(15.4%) from group 2 (p=0.1). Both solutions are useful to prevent surgical wound infections in patients operated by complicated acute appendicitis.